Colombia : directorio de exportadores 1981 = Colombia export directory 1981 (Export Promotion Fund BogotaCO, 1981)
Lists groups of Colombian export products. Provides profiles of exporting companies. Lists main institutions and agencies engaged in Colombia's foreign trade and Colombia's diplomatic and consular missions abroad. Contains, inter alia, statistics on the country's main economic indicators.
Text in Spanish and English